Transcutaneous Auricular Neurostimulation (tAN): A Novel Adjuvant Treatment in Neonatal Opioid Withdrawal Syndrome - Jenkins, Dorothea D.; Khodaparast, Navid; O’Leary, Georgia H.; Washburn, Stephanie N.; Covalin, Alejandro; Badran, Bashar W. (Frontiers in Human Neuroscience, 2021)
Maternal opioid use during pregnancy is a growing national problem and can lead to newborns developing neonatal opioid withdrawal syndrome (NOWS) soon after birth. Recent data demonstrates that nearly every 15 minutes one baby is born suffering from NOWS in the United States. The primary therapeutic option to treat NOWS is opioid replacement therapy, commonly oral morphine, which has neurotoxic effects on the developing brain. There is an emergent need for non-opioid treatments for NOWS. Transcutaneous auricular neurostimulation (tAN), a novel and non-invasive form of electrostimulation, may serve as a promising alternative to morphine. tAN is delivered via a multichannel earpiece electrode targeting two cranial nerves - the vagus and trigeminal nerves. Prior research suggests that tAN exerts an anxiolytic effect on the body by releasing endogenous opioids and reduces withdrawal symptoms in adults actively withdrawing from opioids. In this first-in-human prospective, open-label trial, we investigated tAN as an adjuvant to morphine therapy in eight infants > 33 weeks gestational age suffering from NOWS and receiving oral morphine treatment. tAN was delivered up to four times daily for a maximum of 12 days. The primary outcome measures were safety (e.g., heart rate monitoring, Neonatal Infant Pain Scale (NIPS), and adverse events such as skin irritation) and morphine length of treatment (LOT). tAN was well-tolerated and resulted in no unanticipated adverse events. Comparing to the national average of 23 days, the average oral morphine LOT was 13.3 days (median 9 days) and average LOT after tAN initiation was 7 days (median 6 days). This preliminary data suggests that tAN is safe and may serve as a promising alternative adjuvant for treating NOWS and reducing the amount of time an infant receives oral morphine.